Význam hybridizacných metód v mikrobiologickej diagnostike: DNA sondy a PCR - Jusková, E; Ciznár, I (Ceskoslovenska epidemiologie, mikrobiologie, imunologie, 1992)
The authors give an account of hybridization methods, in particular DNA probes and the polymerase chain reaction (PCR) and their application in microbiological diagnosis. They deal with the principle of the two methods and their applications in the diagnosis not only of genera and species but also different factors of pathogenicity and virulence. The authors mention the advantages and disadvantages of radioactively and non-radioactively labelled probes such as PCR. They draw attention to the perspective application of these methods in research and diagnostic laboratories.
Keywords: virové nemoci; Bacterial Infections; DNA sondy; Virus Diseases; mikrobiologické techniky; DNA Probes; polymerázová řetězová reakce; Polymerase Chain Reaction; Microbiological Techniques; bakteriální infekce